Pengaruh Faktor Makroekonomi Terhadap Migrasi Tenaga Kerja Indonesia dalam Perspektif Ekonomi Islam: (Studi Studi Kasus Tahun 1995-2024) - Anisa Putri; M. Wakhid Musthofa; Muhammad Ghafur Wibowo (Lembaga Pengembangan Kinerja Dosen, 2026)
The disparity between education levels and job availability in Indonesia, coupled with the suboptimal impact of Gross Domestic Product (GDP) dynamics on unemployment figures, primarily drives the increase in labor migration abroad. This study aims to analyze the extent to which education level, unemployment rate, and GDP influence the decision of Indonesian citizens to migrate overseas during the 1995-2024 period. A quantitative approach employing multiple linear regression analysis (OLS method) was utilized, supported by Eviews 12 software and secondary data from the Central Statistics Agency (BPS) and World Development Indicator. The research findings indicate that, simultaneously, education level and unemployment significantly affect migration. However, when examined partially, only education level and unemployment show a significant influence, while GDP does not significantly impact migration. The results suggest that improving education quality and aligning it with job creation strategies within Indonesia could reduce the trend of labor migration. Ultimately, policies aimed at both enhancing education and fostering employment opportunities domestically could mitigate the flow of labor migration abroad.